Economic Contributions And Employment Effects Of Sari-Sari Stores In Dumaguete City (International Journal of Environmental Sciences, 2025)
Sari-sari stores are vital micro-enterprises in Dumaguete City, significantly contributing to the local economy through income generation and employment. This study examines their economic impact, focusing on household income, job creation, and their role in supporting community commerce. It analyzes the demographic profiles of store owners and employees, identifies challenges in sustaining these businesses, and evaluates strategies to address such challenges.Additionally, the research explores the relationships between sari-sari store income and key factors, including the demographic characteristics of respondents, employee income, and operational challenges. By investigating these connections, the study offers insights into how sari-sari stores operate within Dumaguete’s informal economy and contribute to its overall resilience.The findings underscore the critical role of sari-sari stores in promoting economic development and fostering social cohesion. Despite facing challenges such as resource limitations, market competition, and restricted access to financing, store owners demonstrate innovative strategies to sustain their businesses.This study provides actionable recommendations for strengthening the sustainability of sari-sari stores, emphasizing their potential to drive inclusive economic growth. Policymakers, business owners, and community leaders are encouraged to support these micro-enterprises to enhance livelihood opportunities and contribute to Dumaguete City’s economic resilience.